Current status of robot-assisted surgery implementation in endometriosis centers: an international multicentric cross-sectional study - Krentel, Harald; Samartzis, Nicolas; Kalaitzopoulos, Dimitrios Rafail; Constantin, Alin Stefan; Schweppe, Karl-Werner; Metzler, Julian Matthias; Andrikos, Dimitrios; Witzel, Isabell; De Wilde, Rudy Leon; Keckstein, Jörg; Burla, Laurin (Archives of gynecology and obstetrics, 2025)
PURPOSE: The surgical treatment of endometriosis, which is routinely performed by minimally invasive approach, is developing towards an increasing complexity in deep endometriosis. While RAS appears to be gaining importance, there are few real-life data on its use for patients with endometriosis. The aim of this study is to investigate the current use of RAS in certified endometriosis centers in Central Europe. METHODS: In this international multicentric cross-sectional study, an online branching survey was sent to certified endometriosis centers in Austria, the Czech Republic, Germany, and Switzerland. This survey contained 47 questions including proportion of use, indications, advantages and barriers, technical aspects, and training in RAS. RESULTS: Of the 97 centers contacted, 66% (n = 64) participated. RAS is used for the treatment of endometriosis in 60.8% (n = 31) of the centers with access to a SR, which corresponds to 48.4% of all participating centers. In Austria, 81.8% (n = 9) of centers have SR access, respectively, 88.9% (n = 8) use RAS for endometriosis; in Switzerland, 91.6% (n = 11) and 36.4% (n = 4); and in Germany, 74.4% (n = 29) and 62.1% (n = 18). The reported advantages of RAS include precision (80%, n = 40), instrument mobility (74%, n = 37), and visualization (72%, n = 36). Compared to CLS, RAS is preferred in multidisciplinary cases (84.6%, n = 22), and overweight patients (61.5%, n = 16) and deep endometriosis (61.5%, n = 16). Specific anatomical indications for RAS vs. CLS include FU (57.7%, n = 15), C (53.9%, n = 14), and FB (50%, n = 13) (#Enzian classification). Patient outcomes of RAS compared to CLS are rated as advantageous in 69.2% (n = 18). The main barriers for RAS for centers without an SR include costs (100%, n = 12) and lack of scientific evidence (33.3%, n = 4). 69.2% (n = 18) have dedicated robotic teams, 42.3% (n = 11) have a second console, 69.2% (n = 18) have a simulator, and 34.6% (n = 9) have training programs. A total of 65.4% (n = 17) believes that RAS will replace CLS in selected cases, and 73.1% (n = 19) would prefer RAS if costs were equal. CONCLUSION: This study demonstrates that RAS is already being used in approximately half of the participating endometriosis centers. While the proportion of RAS procedures compared to CLS is increasing, it still remains comparatively low. Country-specific differences in the use of RAS are evident and are most likely linked to healthcare system structures. Participating centers report both technical and general surgical advantages, as well as specific benefits in cases of deep endometriosis. The main barriers include costs and a lack of scientific evidence. Further research is needed to evaluate the long-term role of RAS in the management of endometriosis.
Keywords: endometrióza; Germany; průzkumy a dotazníky; Female; MIS; Laparoscopy; Deep endometriosis; Robotic Surgical Procedures; ženské pohlaví; průřezové studie; Surveys and Questionnaires; Switzerland; Minimally invasive surgery; laparoskopie; Endometriosis; Švýcarsko; lidé; Austria; RAL; Německo; RAS; Robotic surgery; MIGS; Robotic-assisted surgery; Robot-assisted laparoscopy; Cross-Sectional Studies; Czech Republic; Robot-assisted surgery; Česká republika; Endometriosis surgery; Endometriosis centers; roboticky asistované výkony; Rakousko; Humans